Super-resolution imaging reveals the evolution of higher-order chromatin folding in early carcinogenesis - Jianquan Xu; Hongqiang Ma; Hongbin Ma; Wei Jiang; Christopher A. Mela; Meihan Duan; Shimei Zhao; Chenxi Gao; Eun-Ryeong Hahm; Santana M. Lardo; Kris Troy; Ming Sun; et al. (Nature Communications, 2020)
Aberrant chromatin structure is often found in cancer. Here, the authors optimise super-resolution microscopy for pathological tissue and discovered a significant decompaction of chromatin folding in early carcinogenesis prior to tumour formation.